Post-transplant outcomes of standard and extended criteria donation after circulatory death donor lungs categorized by donation after brain death lung criteria. (10th March 2021) - Tanaka, Shin; Campo-Cañaveral de la Cruz, Jose Luis; Barturen, Mariana Gil; Carrasco, Silvana Crowley; Román, Alejandra Romero; León, María Trujillo Sánchez de; Mejía, Lucas Hoyos; Gómez, Jose Manuel Naranjo; Peláez, Mar Córdoba; Calle, Álvaro Sánchez; Redondo, Marina Pérez; Fadul, Christian García; et al.
Abstract:  : OBJECTIVES: Most transplant centres use donation after brain death (DBD) criteria to assess the quality of controlled donation after circulatory death (cDCD) lungs. However, research on the relationship between DBD extended criteria and cDCD lung transplantation outcomes is limited. We investigated the outcomes of using DBD extended criteria donor organs in cDCD lung transplantation, compared to the standard criteria cDCD lung transplantation. METHODS: A retrospective chart review of consecutive cDCD lung referrals to Hospital Universitario Puerta de Hierro-Majadahonda from June 2013 to December 2019 was undertaken. Donors were divided into standard and extended criteria groups. Early outcomes after lung transplant were compared between these groups using the Kaplan–Meier method and log-rank test. RESULTS: Thirty out of 91 cDCD donor lung offers were accepted for transplantation, of which 11 were from standard criteria donors and 19 were extended criteria donors. The baseline characteristics of the 2 recipient groups were similar. There were no differences in the rates of grade 3 primary graft dysfunction at 72 h after lung transplantation (21% vs 18%), duration of mechanical ventilation (48 h vs 36 h), total intensive care unit stay (10 days vs 7 days) and 1-year survival (89% vs 90%). CONCLUSIONS: Carefully selecting cDCD lungs from outside the standard acceptability criteria may expand the existing donor pool with no detrimental effects on lung transplantation outcomes.